About Error in Measuring Oxygen Concentration by Solid-Electrolyte Sensors - V. I. Nazarov; V. G. Malafey (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper evaluates additional errors while measuring oxygen concentration in a gas mixture by a solid-electrolyte cell. Experimental dependences of additional errors caused by changes in temperature in a sensor zone, discharge of gas mixture supplied to a sensor zone, partial pressure in the gas mixture and fluctuations in oxygen concentrations in the air.